2006
DOI: 10.7202/012399ar
|View full text |Cite
|
Sign up to set email alerts
|

Le temps des Gitans… et non celui des Gitanes1. Mondialisation, ethnicité et patriarcat chez les Kaldarari de Roumanie

Abstract: Le temps des Gitans … et non celui des Gitanes. Mondialisation, ethnicité et patriarcat chez les Roms/Tsiganes Kaldarari de Roumanie. Les Tsiganes/Roms Kaldarari de Roumanie pratiquent traditionnellement l’artisanat et le commerce, dans le contexte d’une vie itinérante et en dehors du marché du travail. Par le commerce de récupération de l’aluminium, la mondialisation économique transforme les hommes en « patrons ». L’ancienne complémentarité des tâches masculines et féminines est remplacée par le modèle de l’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…The phenomenon of early marriages was highlighted particularly as a cause of further problems in adulthood, IPV included. Other factors, such as frustration, jealousy and financial problems, were also attributed as causes of IPV (Dan & Banu, 2018; Hasdeu, 2004). Ironically, Roma communities appear to rather oppose violence against women (Dan & Banu, 2018; Vives-Cases et al, 2018), although Kozubik et al (2020) found that prevailing gender stereotypes were a precondition in all IPV cases studied ( N = 20).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The phenomenon of early marriages was highlighted particularly as a cause of further problems in adulthood, IPV included. Other factors, such as frustration, jealousy and financial problems, were also attributed as causes of IPV (Dan & Banu, 2018; Hasdeu, 2004). Ironically, Roma communities appear to rather oppose violence against women (Dan & Banu, 2018; Vives-Cases et al, 2018), although Kozubik et al (2020) found that prevailing gender stereotypes were a precondition in all IPV cases studied ( N = 20).…”
Section: Resultsmentioning
confidence: 99%
“…Although the authors argued that the sample ( N = 288) is representative, it is still small, and therefore, these results need to be interpreted with caution. Further, Hasdeu (2004) conducted a 2-year ethnography with Romanian Roma and underscored the role of frustration as a risk factor in IPV but did not specify the extent of the phenomenon. In addition, Dan & Banu, 2018 addressed domestic violence against Romanian Roma women and found a rather high level of such violence in these families.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…À ce titre, les travaux de Fredrik Barth (1999) sur la construction des « groupes ethniques » montrent comment ces frontières sont socialement construites, mobiles, situationnelles, perméables, mais également conflictuelles. Il s'agit dès lors d'interroger les mécanismes de création et de reproduction des représentations sociales et des pratiques identitaires qui reposent sur la distinction et la séparation de l'autre dans une perspective processuelle (Hasdeu 2007).…”
unclassified